The Prerequisites for Establishing the Republic of Armenia State Policy in the Field of Biosecurity - Vardanyan, Bagrat (YSU Journal of International Affairs, 2024)
In the modern era, the biological factor has assumed a crucial role in almost all spheres of activity of the individual, society, state and nation. The 21st century is unique in its scientific and technical progress and virtualization processes, which were initially notable for their negative aspects. One of the most serious threats is the growth of biological terrorism and biological disasters, which pose a serious threat to the stable functioning and normal development of states, societies and individuals. New directions have been added to the military-political and economic spheres of state competition, defining the place and role of the biosecurity system in the context of the country’s national security. The main objective of the article is to study the priorities, priority areas and problems of the state policy of the Republic of Armenia in the field of biosafety, as well as control and prevention of biological threats and challenges, which are significantly increasing as a result of scientific and technological progress. To achieve the set goals, it is necessary to present the essence of biosafety and define the concept, to study international experience in ensuring biosafety, investigating the feasibility of their application in the process of ensuring biosafety in the Republic of Armenia, and also to consider issues of biosafety development in the Republic of Armenia. According to the World Health Organization (WHO), every year two billion people worldwide become ill with infectious diseases, of which 17 million die. Half of the world’s population lives in areas endemic for infectious diseases or within natural foci. The growth of tourism, labor migration, trade turnover, as well as the evergrowing refugee problem contribute to the spread of infectious diseases and the emergence of epidemics, especially in countries where the level of health infrastructure is low.